An evaluation of Smart Selangor Bus service efficacy / Jezan Md Diah, Noraishah Akhirruddin and Raha Abd Rahman - Md Diah, Jezan; Akhirruddin, Noraishah; Abd Rahman, Raha (2022)
Smart Selangor Bus (SSB) is a free bus service that is a local government initiative as one of the most effective measures for its citizens. It aims to improve the quality and transport system in the state of Selangor. The SSB serves as one of the public transport vehicles carrying passengers around the city without charge regardless of age, occupation, gender or nationality. The purpose of this research is to determine the factors that can contributed to commuter satisfaction and evaluate an effectiveness on subsidized fare free public transport (FFPT) services provided. Data for the study were gathered through questionnaire among passenger of SSB on socio-demographic characteristics, travel behaviour characteristics and question of willingness to changes the mode of transportation and rider's data depends on type of routes from Klang Municipal Council (MPKlang). The Cronbach's Alpha test shows that the value is α>0.7 which is it showed the questionnaire to reach the high reliability. The results of this study show that an effectiveness of SSB is significantly related commuter satisfaction on bus stop cleanliness and comfort, bus cleanliness, comfort and safety of the bus and also punctuality and other facilities and also related to the increase in the number of riders every month. Those factors that can contribute to the commuter satisfaction further affect the willingness of Klang residents to switch to public transport mode options and continue to enjoy this free fare public transport facility and at the same time increase the effectiveness of SSB service. These findings provide a vision for better management to SSB stakeholders, especially to funders namely the MPKlang and the Selangor State government as well as bus service operators and the general public.